Lacustrine record of last millennia eruptions in Northern Chilean Patagonia (45–47°S). (August 2017) - Fagel, Nathalie; Alvarez, Denisse; Namur, Olivier; Devidal, Jean-Luc; Nuttin, Laurence; Schmidt, Sabine; Jana, Patricia; Torrejon, Fernando; Bertrand, Sebastien; Araneda, Alberto; Urrutia, Roberto
Due to its tectonic setting, the Andean Southern Volcanism Zone (SSVZ) is characterized by frequent volcanic activity. Chilean Patagonia lake sediments represent powerful archives of historical and past eruptions since the deglaciation. The lacustrine tephra record is investigated in 10 Holocene sedimentary cores collected in five lakes located along a 45–47° transect through Northern Chilean Patagonia. All the tephras identified by visual observation and strong magnetic susceptibility signal have been characterized for the major chemical composition of their glass shards by microprobe analyses, bulk mineralogical content by x-ray diffraction analyses and grain-size distribution by laser diffraction. Special care has been given to the chronostratigraphical framework in order to determine the age interval for each tephra layer and further to correlate the lacustrine records. The sedimentary age models are based on 210 Pb data and calibrated radiocarbon dates measured on macroremains or reservoir effect-corrected bulk sediment. To present a more complete tephrochronological record, 28 microtephras have been confirmed by their mineralogical signature. Our lacustrine tephra record is compared with the Holocene eruptions registered in both surface deposits and continental, lacustrine and peat bog, environments. The different lacustrine eruption records are discussed according to their origin, age and location (distance from volcanoes, wind direction and dispersion of eruption produced). Our data confirm that Chilean Ande SSVZ tephras are mainly derived from historical and past Hudson eruptions. However, the peculiar low-K2 O signature of the glass shards observed in one tephra layer from the Northernmost lake, Lake Thompson, confirms an influence from some other SSVZ volcanoes with low-abundance magma type, such as Maca and Cay. Our tephrochronological data compliment the database for volcanic activity in Chile bringing new information essential for the running discussion on the temporal distribution of eruptions over the Holocene.